2000
DOI: 10.1017/s1355838200991544
|View full text |Cite
|
Sign up to set email alerts
|

Expanded CUG repeat RNAs form hairpins that activate the double-stranded RNA-dependent protein kinase PKR

Abstract: Myotonic dystrophy is caused by an expanded CTG repeat in the 39 untranslated region of the DM protein kinase (DMPK) gene. The expanded repeat triggers the nuclear retention of mutant DMPK transcripts, but the resulting underexpression of DMPK probably does not fully account for the severe phenotype. One proposed disease mechanism is that nuclear accumulation of expanded CUG repeats may interfere with nuclear function. Here we show by thermal melting and nuclease digestion studies that CUG repeats form highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
216
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 227 publications
(225 citation statements)
references
References 39 publications
9
216
0
Order By: Relevance
“…Several CUG-repeat-binding proteins have been identified including muscleblind, CUG-binding protein (CUG-BP), elav-type RNA binding protein 3 (ETR-3), which is 78% identical to CUG-BP, and protein kinase R (PKR; Timchenko et al 1996;Lu et al 1999;Miller et al 2000;Tian et al 2000). The proteins from three human muscleblind genes (Fardaei et al 2002) are homologs of a protein required for development of muscle and photoreceptor cells in Drosophila (Begemann et al 1997;Artero et al 1998).…”
Section: Myotonic Dystrophymentioning
confidence: 99%
“…Several CUG-repeat-binding proteins have been identified including muscleblind, CUG-binding protein (CUG-BP), elav-type RNA binding protein 3 (ETR-3), which is 78% identical to CUG-BP, and protein kinase R (PKR; Timchenko et al 1996;Lu et al 1999;Miller et al 2000;Tian et al 2000). The proteins from three human muscleblind genes (Fardaei et al 2002) are homologs of a protein required for development of muscle and photoreceptor cells in Drosophila (Begemann et al 1997;Artero et al 1998).…”
Section: Myotonic Dystrophymentioning
confidence: 99%
“…7), most likely to diminish their ability to interact with doublestranded RNA-binding proteins. Transcripts containing the uninterrupted double-stranded CAG repeats were shown earlier to activate the RNA-dependent protein kinase PKR (46,47), and form a complex with the specific 63 kDa CAG repeatbinding protein (48). Such interactions resulting in protein activation or sequestration were considered as effects potentially triggering the mechanism of RNA-mediated pathogenesis also in a group of neurodegenerative diseases caused by the CAG repeat expansions (17)(18)(19)(20)(21)49).…”
Section: Structures Of the Sca1 Transcripts Are The Same In Cellularmentioning
confidence: 99%
“…They suggested that CUG hairpins are the most stable structures formed and also that the DMPK mRNAs are sterically impeded from transport through nuclear pores, by giant hairpins or hairpin clusters formed by CUG repeats above a limit size (44 or less) (Koch & Leffert, 1998). Further thermal melting and nuclease mapping studies indicated that CUG repeats form highly stable hairpins (Tian et al, 2000). Michalowski et al, used electron microscopy to provide the first visual evidence that the DMPK mRNA expansion forms an RNA hairpin structure (Michalowski et al, 1999).…”
Section: Rna Nuclear Retentionmentioning
confidence: 99%